Serum Adalimumab Levels After Induction Are Associated With Long-Term Remission in Children With Inflammatory Bowel Disease - Lucafò, Marianna; Curci, Debora; Bramuzzo, Matteo; Alvisi, Patrizia; Martelossi, Stefano; Silvestri, Tania; Guastalla, Veronica; Labriola, Flavio; Stocco, Gabriele; Decorti, Giuliana (Frontiers in Pediatrics, 2021)
Introduction: Adalimumab is effective in inducing and maintaining remission in children with inflammatory bowel diseases (IBD). Therapeutic drug monitoring is an important strategy to maximise the response rates but data on the association of serum adalimumab levels are lacking. This study aimed to assess the association of adalimumab concentrations at the end of induction and early during maintenance for long term response. Materials and methods: Serum samples for adalimumab levels measurement were collected during routine visits between adalimumab administrations and therefore not necessarily at trough, both during the induction (week 4 ± 4) and maintenance phases (week 22 ± 4, week 52 ± 4, week 82 ± 4). Adalimumab and anti-adalimumab antibodies were measured retrospectively using enzyme-linked immunosorbent assays (ELISA). Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. Results: Thirty-two children (median age 14.9 years) were enrolled. Sixteen, 15, 14 and 12 patients were in remission at week 4, 22, 52 and 82, respectively. Median adalimumab concentration was higher at all time points in patients achieving sustained clinical remission. Adalimumab levels correlated with clinical and biochemical variables. Adalimumab concentration above 13.85 and 7.54 µg/ml at week 4 and 22 are associated with remission at week 52 and 82. Conclusions: Adalimumab non-trough levels are associated with long-term response in pediatric patients with IBD.